Cardiovascular syphilis-associated acute myocardial infarction: A case report. Issue 7 (19th February 2021) - Li, Xiangdong; Wang, Xue; Wang, Zhiyuan; Du, Beibei; Mao, Cuiying; Meng, Heyu; Meng, Fanbo; Yang, Ping
Abstract: Rationale: In recent decades, the incidence of advanced syphilis has declined due to early recognition and the application of effective antibiotics. Advanced syphilis often manifests in the cardiovascular system as simple aortitis, aortic valve insufficiency, coronary artery stenosis or obstruction, Aortic aneurysm and mucinous myocarditis. In most case reports on the subject, acute myocardial infarction caused by syphilis was reported to be due to aortic valve insufficiency and coronary stenosis as a result of the involvement of the aorta. Patient concerns: The patient was a 48-year-old woman. She was admitted to our hospital because of intermittent upper abdominal pain with chest tightness for 3 hours. The patient reported a past syphilis infection, when she was hospitalized for hysteromyoma surgery four years ago, and had no related treatment. Diagnosis: According to the characteristics of coronary angiography and results of lab tests and echocardiography, she was finally diagnosed with myocardial infarction associated with syphilis. Interventions: At the first diagnosis of syphilis, the patient did not received antibiotics treatment. After the diagnosis of myocardial infarction, she received the percutaneous coronary intervention (PCI) operation assisted by extracorporeal membrane oxygenation (ECMO) technology, successfully got drug -eluted stents in right coronary artery ostium and left main ostium. Then the patient received penicillin to treat the syphilis infection. Outcomes: After coronary revascularization, the cardiac function of the patients was gradually improved, and the left ventricular ejection fraction was gradually improved after combined with optimized drug therapy. Lessons: The cardiovascular system is often involved in the stages of advanced syphilis with severe complications like myocardial infarction. Standard treatment should be given as soon as syphilis is diagnosis. For stenosis of coronary ostium, the PCI assisted by ECMO technology did not only ensure the effectiveness of the treatment, but also reduce the surgical risk of the patient. This case indicated the effectiveness of ECMO-assisted PCI, and thus may provide a reference for future patient treatment.